Immunogenicity risk assessment for tailored mitigation and monitoring of biotherapeutics during development: recommendations from the European Immunogenicity Platform - Grudzinska-Goebel, Joanna; Benstein, Karin; Bloem, Karien; Cowan, Kyra J.; Gorovits, Boris; Jadhav, Maria; Janssen, Melody; Jawa, Vibha; Kiessling, Andrea; Kramer, Daniel; Kromminga, Arno; van der Linden, Marcel; et al. (Frontiers in Immunology, 2025)
Bringing safe and effective drugs to patients is of utmost importance for the pharmaceutical industry, with immunogenicity (IG) being a critical factor that influences both aspects. Biotherapeutics can elicit unwanted immune responses, potentially leading to (severe) safety implications, reduced patient benefits, and may result in termination of development. Therefore, understanding IG risks throughout drug development is essential for both drug developers and health agencies (HAs). The Immunogenicity Risk Assessment (IRA) facilitates the identification of IG risk factors and allows the establishment of effective mitigation and monitoring strategies. In this publication, the European Immunogenicity Platform (EIP) presents a comprehensive IRA framework aligned across pharmaceutical industry, emphasizing its significance in product development - from early de-risking to bioanalytical monitoring and mitigation measures during clinical trials. The EIP also provides an updated list of IG risks, offers distinct recommendations for assigning overall IG risk levels prior to the start of clinical development and highlights business considerations within this assessment.